METHOD OF INTENSIFIED MARINATION OF MEAT AND ITS INFLUENCE ON THE ORGANOLEPTIC INDICATORS OF THE PRODUCT - BATRACHENKO, OLEXANDR; OREL, VICTOR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The marinating process allows to significantly improve the organoleptic characteristics of meat and it is widely used in industry and in everyday life. However, despite the numerous studies of the meat marinating process and known methods of its implementation, the intensification of meat marinating without the use of complex technical devices remains relevant, both for the meat processing industry and for catering establishments. The aim of the work is to substantiate the intensified method of marinating meat using perforated diffusion channels and to study its effect on the organoleptic characteristics of the finished product. We have developed a new method of intensification of meat marinating. According to it, perforated diffusion channels (PDCs) are used to supply the marinade by gravity into a piece of meat, which have developed perforations on their side cylindrical walls. The use of such PDCs creates conditions for the fastest penetration of the marinade throughout the entire thickness of the piece of meat and promotes its distribution around the PDC itself. As a result, the duration of the marinating process is significantly reduced, both in comparison with traditional marinating and in comparison with the use of tubular elements. The conducted studies have shown the following. The use of perforated diffusion channels allowed to significantly, by 1.5-5 times, reduce the duration of the marinating process of beef steaks in comparison with the classical method of marinating (control samples). The higher density of the installation of the MPC in the test sample corresponds to a clearly pronounced reduction in the duration of the marinating process. According to the ratio "marinating duration / number of MPCs used", we consider the best mode, according to which samples No. 2 were marinated. To achieve the highest organoleptic indicators, which will be significantly higher compared to classical marinating, we recommend using the mode, according to which samples No. 4 were marinated.